(untitled) (Research, Society and Development, 2021)
The objective was to analyze the temporal variability of the recovery capacity in the ottobasin region of the Itapemirim, Benevente and Itabapoana Rivers, south of Espírito Santo, thus identifying the dry and rainy periods through the Rain Anomaly Index. Ten rainfall stations belonging to the National Institute of Meteorology (INMET) were selected, whose series ranged from 1991 to 2020. Periods with positive and negative anomalies were identified in all stations. The Vila Nova Maravilha, Ibitirama and Domingos Martins (DNOS) stations stand out, which have been classified as extremely dry in recent years. On the other hand, the Ponta da Fruta, Fazenda Monte Alegre, Santa Cruz - Caparaó and Burarama stations have a more favorable water condition, in general, there is an alternation between years with positive and negative anomalies. A possible “inflection point” was identified in 2015, from which a likely change in rainfall pattern occurs, when analyzing the average Rain Anomaly Index. The average annual transition of the region was 1466.4 mm, with variations between 975.6 mm (Domingos Martins station (DNOS), natural dry zone - southeast of the Itapemirim River ottobasin) to 2010,1 mm (Vila Nova Maravilha station, rainy natural zone - southwest of ottobacia Rio Benevente). The Burarama station (central region of the Itapemirim River ottobasin) stands out, which despite being located in the natural dry zone, had the second highest total precipitation (1659.6 mm). The months of February, April, May, June, July and September, total precipitation below the average for the region, whose value was 122.2 mm.